Fostering Self-acceptance in Adolescents Through Regular Practice of Surya Namaskara Yoga - Martini, Ni Luh Ayu; Asli, Luh (Jayapangus Press, 2023)
The issue of self-acceptance in young person is still a concern of researchers. It is sad when teenagers are busy looking for happiness outside themselves and forget the happiness from within. Surya Namaskara Yoga is a part of Yoga teachings and easy to practice in everyday life, especially for teenagers. They can practice yoga to cultivate self-acceptance . The purpose of this article is to find how to cultivate self-acceptance in adolescents through the regular practice of Surya Namaskara Yoga. The method used is a qualitative method, by using qualitative descriptive analysis. The result of this article is adolescents able to understand themselves with all psychological processes and their weakness. It’s can increase self-acceptance . The inability of adolescents to cultivate self-acceptance will have an impact on their quality of life. Surya Namaskara Yoga if practiced earnestly and consistently can align themselves with cosmic traits and refresh life with a growing awareness for better self-acceptance . The conclusion is by practicing Surya Namaskara Yoga every morning can awaken the solar aspect of human nature and release this vital energy for raise of a higher consciousness. They can practice Surya Namaskara Yoga every day for balance and increase mental stability so that can be fosters better self-acceptance.